On Some Further Generalizations of Strong Convergence in Probabilistic Metric Spaces Using Ideals - Pratulananda Das; Kaustubh Dutta; Vatan Karakaya; Sanjoy Ghosal (Abstract and Applied Analysis)
Following the line of (Das et al., 2011, Savas and Das, 2011), we make a new approach in this paper to extend the notion of strong convergence and more general strong statistical convergence (Şençimen and Pehlivan, 2008) using ideals and introduce the notion of strong ℐ- and ℐ*-statistical convergence and two related concepts, namely, strong ℐ-lacunary statistical convergence and strong ℐ-λ-statistical convergence in a probabilistic metric space endowed with strong topology. We mainly investigate their interrelationship and study some of their important properties.